Infection control interventions against carbapenem-resistant Acinetobacter baumannii and Klebsiella pneumoniae in an Iranian referral university hospital: A quasi-experimental study - Mojtaba Akbari; Christian G. Giske; Malihe Alenaseri; Ahmad Zarei; Narjes Karimi; Hamid Solgi (Antimicrobial Resistance and Infection Control)
Abstract Background In the past decades, the prevalence of carbapenem-resistant Gram-negative bacteria (CR-GNB) has increased on a global scale. Here, we outline the infection prevention and control (IPC) interventions for addressing the prevalence of carbapenem-resistant Acinetobacter baumannii (CRAB) and carbapenem-resistant Klebsiella pneumoniae (CRKP). Methods A quasi-experimental study design was performed during the seven periods of 6-months from September 2018 to September 2021 in a large ICU in an Iranian hospital. IPC interventions were implemented from period 2 onward, with the exception of period 4 (March-September 2020) due to COVID-19 pandemic-related service disruptions. CRKP and CRAB prevalence and antibiotic resistance of GNB were compared across the seven periods. Results In total, 1,862 GNB isolates were identified across seven periods, with K. pneumoniae (41%) being the most prevalent pathogen, followed by Escherichia coli (24.6%) and A. baumannii (14%). The highest antibiotic resistance rates, including 65.5% for meropenem, were observed during the fourth period. From September 2019 to March 2022, 178 CRKP and 97 CRAB isolates were identified, with infection rates of 78.1% and 62.9%, respectively. Following IPC interventions, a significant reduction in CRKP and CRAB prevalence was noted in the second and third periods, although an increase occurred during the fourth period. By the seventh period, the lowest prevalence of CRKP (26 isolates) and CRAB (5 isolates) was observed. Finally, a moderate inverse correlation (-0.571) was found between hand hygiene compliance and mortality incidence. Conclusion The implementation of targeted IPC interventions significantly reduced the prevalence of CRKP and CRAB infections in the ICU, demonstrating their effectiveness in controlling antibiotic-resistant pathogens. However, the resurgence of these infections during the COVID-19 pandemic highlights the need for continuous monitoring and adaptation of IPC strategies. Ongoing training and adherence to hygiene protocols are essential to sustain improvements and prevent future outbreaks. Our findings underscore the importance of proactive infection control measures in managing antibiotic resistance in critical care settings.